O Clube de Matemática como espaço formativo: futuros professores desenvolvendo ações de compartilhamento na organização do ensino de matemática - Zwirtes, Andresa Kaspary (2024)
This dissertation, linked to the research line Teaching, Knowledge and Professional Development of the Graduate Program in Education at the Federal University of Santa Maria (UFSM), has as main objective to investigate actions of a project that involves sharing seeking to identify its training potential for future teachers in a specific context of organization of mathematics teaching for the early years of elementary school. The research was directed, more specifically, to the UFSM Mathematics Club having as subjects four academics, one of the Degree in Geography and three of the Bachelor’s Degree in Mathematics, project fellows. With regard to the theoretical and methodological approach that makes up the guiding dimension of this research, the principles adopted were the: Historical-Cultural Theory; Theory of Activity; Teaching Guidance Activity. Regarding the executor dimension, data from records - Google Forms questionnaire, audio recordings, reflective sessions, researcher’s field diary, were analyzed through the establishment of three axes of analysis aiming to apprehend the phenomenon in its totality: 1) Study; 2) Planning; 3) Development and evaluation of teaching actions. In the first axis, which sought to verify perceptions of future teachers with respect to the study developed in the Club of Mathematics, it was evidenced that this allows the attribution of a new sense to the organization of teaching by the contributing to their learning process for teaching. In the second axis, which aimed to understand how future teachers perceived the action of building a planning for a class of third year of the first years of elementary school having as guiding principle the Teaching Guidance Activity, identified indicators of learning for teaching listed by future teachers linked to the meanings coincided with the social meaning of the action of planning as an organizational tool guiding. In the third axis, it was intended to analyze how the process of future teachers put themselves as teachers during the development of planned proposals and evaluate the developed teaching actions, it was found that in light of feelings of satisfaction due to the involvement of children and discomfort associated with little familiarity with the school context, the senses related to evaluation approached their social meaning. Finally, from this study it is possible to reiterate that the actions of a space have the potential to contribute in teaching learning by enabling future teachers to develop different actions that are part of this medium to be carried out in a shared way. And this observation confirms the possibility of understanding sharing as both a premise (initial principle adopted) and a product (result that enables learning).